The Guarantees of Human Rights and Freedoms in the European Union: The Experience for Ukraine - NOVITSKY, Vladislav V. (Journal of Advanced Research in Law and Economics, 2019)
The article examines the issues of guarantees of human rights and freedoms in the European Union, in particular, their concepts and varieties. The attention is focused on some differences in the understanding of the nature of human rights guarantees in domestic legal doctrine and in European law. In general terms, the content of the system of guarantees of human rights and freedoms operating within the European Union is revealed. It is concluded that within the European Union such guarantees always have a legal nature, since their implementation in public practice it is associated with the existence of relevant norms enshrined in both supranational EU law and in the law of the national member states of the EU.